Pengaruh Pupuk Alami Dari Air Kulit Pisang Terhadap Perkecambahan Benih Jagung (Zea Mays) - Nurul Hamidah Dohona (Jurnal Ilmu Pertanian dan Perikanan, 2025)
This research is an experimental study with a qualitative approach aimed at determining the effect of banana peel water concentration on the germination of corn seeds. The study was conducted in Hilimbaeodesolo, Gunungsitoli City, over four days using three different treatments: 25%, 50%, and 100% concentrations of banana peel water, each repeated three times. The seeds were soaked for 36 hours, and observations were made on the emergence of radicles, the number of germinated seeds, and signs of decay. The results showed that the 50% concentration was the most effective treatment, producing healthy sprouts and the highest number of germinated seeds. The 25% concentration showed limited early growth, while the 100% concentration caused the seeds to rot due to excessive fermentation. The study concluded that banana peel water concentration affects germination success, with a balanced concentration (50%) being the most optimal to support early growth. It is recommended to use moderate concentrations and conduct further testing on plant growth after the germination phase.